The Fragility of Workers in Temporary Employment Agreements in Indonesia - Sandra Imam Mustofah (Universitas Muhammadiyah Sidoarjo, 2018)
Application employee for Working Agreement of Certain Time is a right step for the company in saving the production process, so that the company will be more benefited with the existence of such a specific time working agreement. In the legislation of the law has arranged employee a certain time work agreement, one of them related to the type and character of the work because of frequent violations in the implementation . This research aims to what form of legal protection for workers of certain time work agreement related to the type and characteristic of the work. This research uses normative method with approach of law. Protection for employee contract who get jobs that are not in accordance with the rules of the legislation related to the type and nature of work is to switch the status of being an unspecified worker. the legal protection of employee contract are jamsostek, PP, and PKB. This research is helpful as a reference of legal practitioners, increase the knowledge and insight of the community related to legal protection of contract workers.